Spindle vibration signal extraction method based on improved all phase Fast Fourier Transform. Issue 1 (March 2020) - Wang, Z; Du, SY; Roşca, LC
Abstract: In the modern processing technology, the machine tool plays an irreplaceable role as the main processing tool, and its machining accuracy directly affects the processing quality of the part. Because the spindle vibration caused by the rotor mass imbalance will seriously affect the machining accuracy of the machine tool, it is necessary to dynamically balance the spindle. The key step of dynamic balancing is to accurately extract the characteristics of the vibration signal, the phase of the vibration signal of the spindle was extracted by the all phase fast Fourier transform, the amplitude of vibration signal was extracted by cross correlation analysis, the results are applied to the influence coefficient method to realize the dynamic balance of spindle vibration The results show that the vibration signal feature extraction method combined with the results of the two extraction methods has high precision and stability.